PENGARUH PENERAPAN GOODiCORPORATEiGOVERNANCE TERHADAPiAUDIT REPORTiLAG (StudiiPada Perusahaan Pertambangan Di Bursa_Efek Indonesia Tahun 2014-2018) - Sukmawati, Sukmawati; Saptantinah P.A, Dewi; Harimurti, Fadjar (Universitas Slamet Riyadi, 2021)
Thissresearch wassconducted to know the effect of the implementation ofgood corporateegovernance on audit report lag in companies listed on Bursa EfekIndonesia in 2014-2015. This research uses secondary data abtained from thecompany’s financial statement. The technique to get sample use purposivesampling.The result of T count -2,253 with p-value 0,01 < 0.05 means that there is anegative and significant influence on the size of the audit committee (X1) on the auditreport lag (Y). H acyl t -2,382 with a p-value of 0,019 > 0.05 means that any negativeeffects and significant institutional ownership (X2) on the audit report lag(Y). H acyl tcount -2,059 with a p-value of 0,042 < 0,05 means there is a negative and significanteffect of the independent board of commissioners (X3 ) against audit report lag (Y). H acylt count -3,569 with a p-value of 0,001 < 0,05 means there is a negative and significanteffect of the size of the board of commissioners (X4 ) against audit report lag (Y). F testresults of 8,293 with a p-value of 0.000 < 0.05, which means that simultaneously variablethe size of committee audit (X1), Institutional ownership (X2), the independent board ofcommissioners (X3), and size of the board of commissioners (X4) have a significant effecton audit report lag (Y) . The determination test shows the value of Adjusted R Square0,200 concluded that the audit report lag variable can be explained by the fourindependent variables the size of committee audit, Institutional ownership, theindependent board of commissioners, and size of the board of commissioners because theremaining Adjusted R Square 20% (100%-20% = 80%) isSexplainedDbyD the causes -Dother causes Soutside theEmodel.